2016
DOI: 10.1155/2016/4685976
|View full text |Cite
|
Sign up to set email alerts
|

High Interleukin-12 Levels May Prevent an Increase in the Amount of Fungi in the Gastrointestinal Tract during the First Years of Diabetes Mellitus Type 1

Abstract: The objective of the research was to investigate serum levels of interleukin-12 (IL12) in relation to percentage of yeast-like fungi colonies residing in the gastrointestinal tract in children and adolescents with type 1 diabetes mellitus (T1DM). The study involved 83 children and adolescents, including 53 T1DM patients and 30 healthy control subjects. In the studied population biochemical tests were performed and yeast-like fungi were identified in the faeces. Moreover, IL12 absorbance was measured and measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Also, this higher growth may disrupt the ecological balance of intestinal flora, which occurs in type 1 DM [37]. Regarding the gastrointestinal colonization, Kowalewska et al [38] studied the serum levels of interleukin-12 (IL12) in relation to the percentage of yeast-like fungi colonies residing in the gastrointestinal tract in children and adolescents with DM type 1. Results showed that high IL12 levels can inhibit infection with yeast-like fungal colonizing the gastrointestinal tract in children and adolescents with type 1 DM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, this higher growth may disrupt the ecological balance of intestinal flora, which occurs in type 1 DM [37]. Regarding the gastrointestinal colonization, Kowalewska et al [38] studied the serum levels of interleukin-12 (IL12) in relation to the percentage of yeast-like fungi colonies residing in the gastrointestinal tract in children and adolescents with DM type 1. Results showed that high IL12 levels can inhibit infection with yeast-like fungal colonizing the gastrointestinal tract in children and adolescents with type 1 DM.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that high IL12 levels can inhibit infection with yeast-like fungal colonizing the gastrointestinal tract in children and adolescents with type 1 DM. However, further studies are needed to confirm the antifungal activity of IL12 [38].…”
Section: Introductionmentioning
confidence: 99%
“…The levels of TNF-alpha were significantly higher in the young diabetic patients in the study compared to the control group. Some studies have also found an association between cytokine levels and the duration of type 1 diabetes [ 22 , 62 , 63 ]. In the Norwegian Atherosclerosis and Childhood Diabetes prospective study, the analysis of TNF-α and IL-18 levels, among others, showed that the early, low-grade inflammation present in young people with T1D five years after diagnosis persists through ten years of disease, with moderate changes in most inflammatory markers over time [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have shown a significant positive correlation between TNF-α and HbA 1c [ 65 ]. On the other hand, some studies have demonstrated a significant negative correlation between the levels of IL-12 [ 63 ], IL-35 [ 49 ], and HbA 1c levels. Similarly to our results, Al-Dubayee et al found no significant relationship between higher levels of HbA 1c and TNF-α IL-4 or IL-10 and the HbA 1c level [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenesis: Candidal vaginitis is a generic term used for vaginal infections caused by Candida species. Candida albicans is responsible for 90% of vulvovaginal candidiasis; the remaining 10% corresponds to C. glabrata and C. Tropicalis 11 Candida albicans colonizes the genital tract of 10 -55% women in the childbearing age group. Most studies show increased rates of vaginal colonization in women infected with HIV.…”
Section: Chronic Vulvovaginal Candidiasismentioning
confidence: 99%